A preliminary study identifying factors of memorable tourism experience in Mulu National Park, Sarawak - Mahdzar, Mazlina; Shuib, Ahmad; Mohammad Afandi, Syamsul Herman; Ramachandran, Sridar (Institut Kajian Dasar Pertanian dan Makanan, Universiti Putra Malaysia, 2015)
This paper aims to identify potential factors of Memorable Tourism Experience (MTE) which is unique to Mulu National Park (MNP), Sarawak. Review of previous studies in the area of tourism experience and a qualitative research approach was chosen for this study as it offered an avenue to understand of the factors that characterize memorable tourism experience. In-depth interviews were conducted, using a structured questionnaire, to collect data from individuals who are directly related to the national park. A total of 13 individuals were interviewed. The findings proposed a new construct of Memorable Tourism Experience (MTE) which can be used to measure the memorable experiences of tourists visiting Mulu National Park.